(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Scientific activities in the Antarctic regions have increased daily within the last decades to achieve many different projects. The ice sheet over 98% of the Antarctic continent, the coldest, driest, and windiest place in the world and has the largest desert, makes it very difficult to conduct any kind of study and research. Among them, precise hydrographic surveying should be conducted for many different applications that require reliable and accurate positioning. The output from these surveys plays a vital role in understanding sea level changes, global warming, sea ice movement, navigation and many others. The harsh atmospheric and topographic conditions of the region pose additional challenges to surveyors in the use of conventional terrestrial measurement techniques and satellite-based positioning methods (GNSS) to make positioning. Low quality and noisy GNSS observations with low satellite elevations made their positioning vulnerable to cycle slip, multipath, and discontinuity in Antarctica. This study analyses the performance of the post-processed kinematic Precise Point Positioning (PPP) based on the web-based online GNSS processing service for marine surveying in the high-latitude environment. Within this frame, two realistic experiments were carried out on board a ship and zodiac boat during the 6th Turkish Antarctic Expedition (TAE). The results show that the PPP coordinates using an online GNSS processing service provide kinematic positioning with centimetre level of accuracy using a single GNSS receiver. The general results showed that the PPP technique allows for much faster and accurate positioning in remote and high-latitude areas at a lower cost.